Jewish emancipation under attack : its legal recession until the present war - Weinryb, Bernard Dov (New York: American Jewish Committee, 1942)
"by Bernard Dov Weinryb ; Research Institute on Peace and Post-war Problems of the American Jewish Committee Bibliotheek Camille Huysmans"